Cancer at the Dinner Table: Experiences of Psilocybin-Assisted Psychotherapy for the Treatment of Cancer-Related Distress. (September 2017) - Swift, Thomas C.; Belser, Alexander B.; Agin-Liebes, Gabrielle; Devenot, Neşe; Terrana, Sara; Friedman, Harris L.; Guss, Jeffrey; Bossis, Anthony P.; Ross, Stephen
Recent randomized controlled trials of psilocybin-assisted psychotherapy for patients with cancer suggest that this treatment results in large-magnitude reductions in anxiety and depression as well as improvements in attitudes toward disease progression and death, quality of life, and spirituality. To better understand these findings, we sought to identify psychological mechanisms of action using qualitative methods to study patient experiences in psilocybin-assisted psychotherapy. Semistructured interviews were conducted with 13 adult participants with clinically elevated anxiety associated with a cancer diagnosis who received a single dose of psilocybin under close clinical supervision. Transcribed interviews were analyzed using interpretative phenomenological analysis, which resulted in 10 themes, focused specifically on cancer, death and dying, and healing narratives. Participants spoke to the anxiety and trauma related to cancer, and perceived lack of available emotional support . Participants described the immersive and distressing effects of the psilocybin session, which led to reconciliations with death, an acknowledgment of cancer's place in life, and emotional uncoupling from cancer . Participants made spiritual or religious interpretations of their experience, and the psilocybin therapy helped facilitate a felt reconnection to life, a reclaiming of presence, and greater confidence in the face of cancer recurrence . Implications for theory and clinical treatment are discussed.